The Influence of the Principal's Transformational Leadership Style, Work Discipline, Job Satisfaction on Teacher Performance in Bireuen Regency - Yusnita; Marwan; Teuku Salfiyadi (FKIP Universitas Halu Oleo, 2023)
The purpose of this research is (1) to find out whether the Transformational Leadership Style of School Principals influences the Performance of State Vocational School Teachers in Bireuen Regency (2) to find out whether Work Discipline influences Teacher Performance. State Vocational School teacher in Bireuen Regency. (3) find out whether Job Satisfaction influences the performance of State Vocational School teachers in Bireuen Regency (4) determine the simultaneous influence of the Principal's Transformational Leadership Style, Work Discipline, Job Satisfaction on the Performance of State Vocational School Teachers in Bireuen Regency. This research uses a quantitative approach method, a population of 227 people with a sample of 145 people with a proportional random sampling technique using the Slovin formula with an error rate of 5%, data collection techniques likert scale questionnaires and multiple linear regression analysis data processing techniques using SPSS 25. Hypothesis testing results Research using the t test shows that there is no significant influence of transformational leadership style on the performance of State Vocational School teachers in Bireuen Regency. This is indicated by the calculated t value < t table (1.436 < 1.976) and with a significant value of 0.153 > 0.05. Meanwhile, there is a significant influence of work discipline on the performance of State Vocational School teachers in Bireuen Regency. This is shown by the calculated t value > t table (3.477 > 1.976) and with a significance value of 0.000 < 0.05. Meanwhile, teacher job satisfaction influences the performance of State Vocational School teachers in Bireuen Regency with a calculated t value > t table (3.483 > 1.976) and with a significance value of 0.000 < 0.05. And the results of the f test show that there is a significant influence of transformational leadership style, work discipline and teacher job satisfaction on the performance of State Vocational School teachers in Bireuen Regency. The calculated f value > f table (32.052 > 2.668) with a significance value of 0.000 < 0.05. It can be concluded that improving teacher discipline must be further improved, in order to increase teacher performance scores.